Body composition analysis to study long-term training effects in elite male water polo athletes - Melchiorri, G.; Viero, V.; Sorge, R.; Triossi, T.; Campagna, A.; Volpe, S. L.; Lecis, D.; Tancredi, V.; Andreoli, A. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Elite water polo athletes undergo heavy training programs throughout the year, but especially to prepare major competitions, such as the Olympic Games (OG). Optimal athletic performance is a result of many factors, including proper management of the intensity and volume of training, nutrition and recovery between training sessions. When training is excessive in relation to recovery may occur nonfunctional overreaching (NFO). NFO can degenerate into overtraining syndrome resulting in a decrease in athletic performance, with likely changes in body weight and body composition. The aim of this study was to evaluate the relationship between body composition and the tolerance to intense training supported by diet meal plans and to highlight any difference between athletes selected for the OG and not selected ones. METHODS: Twenty-one male elite water polo athletes, 26 to 34 years of age, participated in the study. For three months before the Olympics, athletes have carried out an intense training period based on a detailed program. Only 13 athletes participated to OG (OA), 8 were excluded (NOA). Body weight and height were measured and Body Mass Index was calculated. BC and phase angle was evaluated at the half of first (T0), second (T1), and third (T2) month of training. Also blood analyses were collected at T0 and food intake assessed in all the evaluations. Measurements were carried out at three selected time points throughout the training period (12 weeks), which marked variations in the volume and intensity of the training load. RESULTS: Data analyses showed no statistical difference among the three measurements performed for body weight, body composition and phase angle in all OA group. Furthermore, there was not statistically significant differences between the OA and NOA group for weight, body mass index, body composition and phase angle. CONCLUSIONS: Results of the present study encourage the use of body composition by bioelectrical impedance monitoring system for high-level athletes involved in long and intense training periods to prevent body dehydration and overtraining syndrome. Body cell mass monitoring provides a valuable help to evaluate the effects of training and to prevent any decrease in the performance level.